Whole-genome sequencing of SARS-CoV-2 isolates from symptomatic and asymptomatic individuals in Tanzania - Mziray, Shabani Ramadhani; van Zwetselaar, Marco; Kayuki, Charles C.; Mbelele, Peter M.; Makubi, Abel N.; Magesa, Alex S.; Kisonga, Riziki M.; Sonda, Tolbert B.; Kibiki, Gibson S.; Githinji, George; Heysell, Scott K.; Chilongola, Jaffu O.; et al. (Frontiers in Medicine, 2023)
Background: COVID-19, caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) accounts for considerable morbidity and mortality globally. Paucity of SARS-CoV-2 genetic data from Tanzania challenges in-country tracking of the pandemic. We sequenced SARS-CoV-2 isolated in the country to determine circulating strains, mutations and phylogenies and finally enrich international genetic databases especially with sequences from Africa. Methods: This cross-sectional study utilized nasopharyngeal swabs of symptomatic and asymptomatic adults with positive polymerase chain reaction tests for COVID-19 from January through May 2021. Viral genomic libraries were prepared using ARTIC nCoV-2019 sequencing protocol version three. Whole-genome sequencing (WGS) was performed using Oxford Nanopore Technologies MinION device. In-silico genomic data analysis was done on ARTIC pipeline version 1.2.1 using ARTIC nCoV-2019 bioinformatics protocol version 1.1.0. Results: Twenty-nine (42%) out of 69 samples qualified for sequencing based on gel electrophoretic band intensity of multiplex PCR amplicons. Out of 29 isolates, 26 were variants of concern [Beta (n=22); and Delta (n=4)]. Other variants included Eta (n=2) and B.1.530 (n=1). We found combination of mutations (S: D80A, S: D215G, S: K417N, ORF3a: Q57H, E: P71L) in all Beta variants and absent in other lineages. The B.1.530 lineage carried mutations with very low cumulative global prevalence, these were nsp13:M233I, nsp14:S434G, ORF3a:A99S, S: T22I and S: N164H. The B.1.530 lineage clustered phylogenetically with isolates first reported in south-east Kenya, suggesting regional evolution of SARS-CoV-2. Conclusion: We provide evidence of existence of Beta, Delta, Eta variants and a locally evolving lineage (B.1.530) from samples collected in early 2021 in Tanzania. This work provides a model for ongoing WGS surveillance that will be required to inform on emerging and circulating SARS-CoV-2 diversity in Tanzania and East Africa.